2021
DOI: 10.3389/fphar.2021.612426
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Approach Medicines Litigation: An Action Research Study in Brazil

Abstract: Background: In the last decades, litigation has been increasingly used to access medicines in Brazil. This phenomenon has led to the development of diverse strategies to reduce its negative impact on the organization of pharmaceutical services. In spite of that, managers still face difficulties dealing with lawsuits.Objective: This study aims to report the planning and implementation of strategies to approach medicines litigation in a municipality located in the southeast region of Brazil.Methods: Mixed method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
1
0
3
Order By: Relevance
“…An evaluation of the long-term impact of health spending revealed that The main criterion for granting by the magistrate was the identification of the need for access to the medication or procedure, supported by the plaintiff 's medical report. However, it is often observed that prescribers are unaware of the pharmaceutical products offered by SUS, prescribe non-funded medications (46), and those with higher costs, or even off-label use, a factor identified in a previous study as an "effective therapeutic safety failure" (36). The TSO allows evaluating the demands, determining allowable dispensations in public lists, and identifying where the claims can be obtained, among other details (47) Verification of inadequate personal funds for treatment relies notably on self-declaration (18,22,36).…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of the long-term impact of health spending revealed that The main criterion for granting by the magistrate was the identification of the need for access to the medication or procedure, supported by the plaintiff 's medical report. However, it is often observed that prescribers are unaware of the pharmaceutical products offered by SUS, prescribe non-funded medications (46), and those with higher costs, or even off-label use, a factor identified in a previous study as an "effective therapeutic safety failure" (36). The TSO allows evaluating the demands, determining allowable dispensations in public lists, and identifying where the claims can be obtained, among other details (47) Verification of inadequate personal funds for treatment relies notably on self-declaration (18,22,36).…”
Section: Discussionmentioning
confidence: 99%
“…Ao avaliar os fatores associados aos serviços de saúde, estudo recente concluiu que a população da Região Norte apresenta maior precarização no acesso e que o nível de acesso da Região Sul se aproxima ao da Região Sudeste 21 . Pesquisas têm demonstrado que a litigação para acesso a medicamentos e produtos para a saúde é determinada por aspectos sociais e políticos e que pode agravar a iniquidade no sistema de saúde nos casos em que ações judiciais são movidas por pacientes oriundos do setor privado 15 , 16 , 22 .…”
Section: Discussionunclassified
“…As demandas por esses produtos se juntam às demais, relacionadas aos bens e serviços de saúde que o Estado é obrigado a fornecer por ordem judicial. Esse fenômeno, conhecido como judicialização da saúde, tem gerado desafios e exigido dos Poderes Executivo e Judiciário a criação de estratégias institucionais, como câmaras técnicas e secretarias específicas para reduzir as distorções sociais, econômicas e políticas 15 , 16 . Estudo de base exploratória das decisões do Tribunal de Justiça de Pernambuco (TJ/PE) ressalta a necessidade de os pleitos judiciais serem subsidiados com evidências científicas consistentes para a tomada de decisão do magistrado 17 .…”
Section: Introductionunclassified
“…Catanheide et al, (2016), registram quenão se pode afirmar e nem negarque os medicamentos judicializados seriam por falhas na gestão e/ou em decorrência de uma prescrição de medicamento não incorporado ao Sistema Único de Saúde (SUS); ou seja, fora da lista dos componentes básico, estratégico e especializado da assistência farmacêutica; quiçá, uma estratégia da indústria, não adesão dos prescritores às listas oficiais ou, ainda, por desatualização dessas listas; bem como, também não o comprometimento do orçamento federal, estadual e municipal. Machado et al, (2021), identificaram dentre os medicamentos judicializados, que a prescrição dos medicamentos não contemplava as alternativas terapêuticas do Sistema Público de Saúde, do mesmo modo que Oliveira et al, (2022) identificaram uma prevalência de medicamentos não vinculados a nenhum programa. Souza (2021), apontou que dentre os medicamentos judicializados, 83,3% não estavam incorporados no Sistema Único de Saúde (SUS).…”
Section: Judicialização De Medicamentos Antidepressivosunclassified